PERENCANAAN PERSONAL DAN SISTEM PEREKRUTAN SDM (GURU) DI SEKOLAH - Reni Marliani; Suklani Suklani (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2023)
Every country needs quality and competitive human resources because this has a positive impact on the country's development in various fields. So it should be in planning teacher recruitment carried out by following good processes and procedures, so that what is expected by an institution can be achieved as expected. The purpose of this research is to find out how the personal planning and recruitment system of human resources in schools. This study used descriptive qualitative methods with data collection techniques using literature review. The authors collected information from various sources such as journals, articles, books or other sources relevant to the author's research. The results of this study were 1) that the success or failure of a job or activity will be seen from its management. 2) The functions of management include planning, organizing, actuating and controlling or abbreviated as POAC (planning, organizing, actuating, controlling). 3) Educator Planning is used to determine the number and type of teachers needed. 4) Teacher recruitment can be carried out by the school principal or by the central government, based on teacher shortage data from each regional government